2000
DOI: 10.1016/s0167-8809(99)00137-1
|View full text |Cite
|
Sign up to set email alerts
|

Floristic composition of established vegetation and the soil seed bank in pasture communities under different traditional management regimes

Abstract: The floristic composition of the established vegetation and the soil seed bank in seven herbaceous communities under different traditional management regimes were compared in the Valdeón valley (Picos de Europa, Spain), a valley chosen for study because of its high diversity and non-dominance of any single species which have become increasingly rare in Western Europe as a result of changes in agriculture practices. Although the biological richness in this valley is well know, few studies have been made of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 22 publications
6
23
0
1
Order By: Relevance
“…Here we use the scheme proposed by Thompson et al (1997). In this case, L. multiflorum was classified as having a transitory (viable in the soil for less than one year) to short-term persistent (viable for one to five years) type of seed bank, what agrees with results obtained in other countries (Douglas, 1965;Howe and Chancellor, 1983;López-Mariño et al, 2000).…”
Section: Figure 3 Dynamics Of Annual Ryegrass Vegetation In the 6 (Asupporting
confidence: 75%
See 1 more Smart Citation
“…Here we use the scheme proposed by Thompson et al (1997). In this case, L. multiflorum was classified as having a transitory (viable in the soil for less than one year) to short-term persistent (viable for one to five years) type of seed bank, what agrees with results obtained in other countries (Douglas, 1965;Howe and Chancellor, 1983;López-Mariño et al, 2000).…”
Section: Figure 3 Dynamics Of Annual Ryegrass Vegetation In the 6 (Asupporting
confidence: 75%
“…According to some authors, several cultivated grasses, including Lolium spp., do not have persistent soil seed banks (Douglas, 1965;Thompson and Grime, 1979;Howe and Chancellor, 1983;López-Mariño, 2000), indicating that resowing, observed in improved grasslands, is basically from seeds deposited in the soil in the previous season.…”
Section: Introductionmentioning
confidence: 99%
“…Olano et al [44] considered that the soil seed bank was primarily supplied by the dispersal of seeds from the aboveground vegetation, and in turn it was the seedling resources of the development and succession of aboveground vegetation. Thus, the soil seed bank and vegetation were originally closely correlated with each other [45]. The fate of the vegetation determined the fate of the soil seed bank.…”
Section: Relationship Between Soil Seed Bank and Vegetationmentioning
confidence: 94%
“…The contribution of the seed bank to the regeneration process mainly depends on the management history and structural and compositional development of aboveground vegetation. The composition of the seed bank depends on the production and composition of present and previous vegetation, as well as on the longevity of the seeds under local conditions (López-Mariño et al 2000). Abandoned rice paddies offer an opportunity to restore wetland vegetation and reestablish traditional landscapes (Lee et al 2002), helping to maintain endangered wetland species found in the paddy fields that co-existed with rice cultivation (Fujioka et al 2001;Yamada et al 2007Yamada et al , 2013.…”
Section: Introductionmentioning
confidence: 99%